Systems Neuroscience (Advances in Neurobiology,, 2018)
This edition of Advances in Neurobiology brings together experts in the emerging field of Systems Neuroscience to present an overview of this area of research. Topics covered include: how different neural circuits analyze sensory information, form perceptions of the external world, make decisions, and execute movements; how nerve cells behave when connected together to form neural networks; the relationship between molecular and cellular approaches to understanding brain structure and function; the study of high-level mental functions; and studying brain pathologies and diseases with Systems Neuroscience. A hierarchy of biological complexity arises from the genome, transcriptome, proteome, organelles, cells, synapses, circuits, brain regions, the whole brain, and behaviour. The best way to study the brain, the most complex organ in the body composed of 100 billion cells with trillions of interconnections, is with a Systems Biology approach. Systems biology is an inter-disciplinary field that focuses on complex interactions within biological systems to reveal 'emergent properties' - properties of cells and groups of cells functioning as a system whose actual and theoretical description is only possible using Systems Biology techniques.